STUDI KOMPARATIF KECERDASAN EMOSIONAL TERHADAP KONSEP DIRI SOSIAL - Nadia Arissanti Wardhani; Yusmansyah Yusmansyah; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The research purpose was to find the differences between emotional intelligence of students accelerated and non accelerated trough socialself-concept. The purpose in this study is the difference in emotional intelligence research accelerated and non-accelerated students in socialself-concept. The method used was survey method, with emotional intelligence and social self-concept variable. Based on calculations by two way anova obtained comparative index of emotional intelligence and socialself-concept in accelerated students and non accelerated students that is p= 0.002 with a significance level of 0.05. Since the value of p0.05 then Ha accepted and Ho was rejected. Emotional intelligence level of non acceleration students are higher by 89% when compared with accelerated students by 78%. The level of socialself-concept non acceleration students is higher than 88% of socialself-concepts of accelerated students 34%. Tujuan penelitian untuk mengetahui perbedaan kecerdasan emosional siswa akselerasi dan non akselerasi terhadapkonsepdirisosial. Masalah penelitian adalah perbedaan kecerdasan emosi siswa akselerasi dan non akselerasi pada konsep diri sosial. Penelitian menggunakan metode komparatif dengan pendekatan survey. Berdasarkan hasil perhitungan dengan twowayanova diperoleh indeks komparatif perbandingan kecerdasan emosi dan konsep diri sosial pada siswa akselerasi dan non akselerasi yaitu p=0,002 dengan taraf signifikansi 0,05. Karena nilai p0,05 maka Ha diterima dan Ho ditolak. Tingkat kercerdasan emosi pada siswa non akselerasi lebih tinggi yaitu sebesar 89% bila dibandingkan dengan siswa akselerasi sebesar 78%. Tingkat konsep diri sosial siswa non akselerasi lebih tinggi 88% bila dibandingkan konsep diri sosial siswa akselerasi 34%.Kata kunci: bimbingan dan konseling, kecerdasan emosional, konsep diri sosial